Reliability Assessment of a Health Questionnaire among Sedentary Female University Students - Manmohan Kaur; Rabiya Husain; Anil Kumar Baghel; Dhananjoy Shaw (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Health assessment questionnaires are essential tools for evaluating physical activity, lifestyle patterns, and psychological well-being. Ensuring their reliability is crucial for obtaining consistent self-reported data, particularly among sedentary female university students, who may exhibit unique health behaviours. This study examines the test-retest reliability of a health assessment questionnaire, assessing its stability over time and identifying variations in responses based on participant characteristics. A total of 63 sedentary female college students from the University of Delhi were randomly selected for this study. A standardized Health Questionnaire (HQ), covering seven key components was administered twice with a two-day interval to assess test-retest reliability. After expert validation, 39 variables were analysed. Reliability was evaluated using Pearson’s correlation coefficient, and consistency of responses was further examined through a paired t-test. In the study one variable demonstrated strong reliability (r > 0.70), and 38 variables showed acceptable reliability (0.40 < r < 0.80) with an overall mean reliability coefficient of 0.47. Paired t-test results indicated statistically significant differences (p < 0.05) in 10 variables. The remaining 29 variables did not exhibit significant differences between trials. It is concluded that the Health Questionnaire (HQ) exhibits strong test-retest reliability among sedentary female students, confirming its effectiveness in assessing health-related parameters. Minor inconsistencies observed in certain variables suggest the need for refinement to enhance clarity and accuracy. With further validation, the HQ can serve as a reliable tool for future research and practical health assessments.
Keywords: Female; Health Assessment Questionnaire; Reliability; Sedentary; Test-Retest